G-quadruplex is critical to epigenetic activation of the lncRNA HOTAIR in cancer cells - Xiaohan Qu; Zhen Lin; Janarthanan Jayawickramarajah; John S. Alsager; Emily Schmidt; Kenneth P. Nephew; Fang Fang; Shankar Balasubramanian; Bin Shan (iScience, 2023)
Summary: The cancer-promoting lncRNA HOTAIR has multiple isoforms. Which isoform of HOTAIR accounts for its expression and functions in cancer is unknown. Unlike HOTAIR’s canonical intergenic isoform NR_003716 (HOTAIR-C), the novel isoform NR_047517 (HOTAIR-N) forms an overlapping antisense transcription locus with HOXC11. We identified HOTAIR-N as the dominant isoform that regulates the gene expression programs and networks for cell proliferation, survival, and death in cancer cells. The CpG island in the HOTAIR-N promoter was marked with epigenetic markers for active transcription. We identified a G-quadruplex (G4) motif rich region in the HOTAIR-N CpG island. Our findings indicate that G4s in HOTAIR-N CpG island is critical for expression of HOTAIR-N in cancer cells. Disruption of G4 may represent a novel therapeutic approach for cancer. The transcriptomes regulated by HOTAIR-N and Bloom in cancer cells as provided herein are important resources for the exploration of lncRNA, DNA helicases, and G4 in cancer.